2021
DOI: 10.3390/genes12121852
|View full text |Cite
|
Sign up to set email alerts
|

SESN3 Inhibited SMAD3 to Relieve Its Suppression for MiR-124, Thus Regulating Pre-Adipocyte Adipogenesis

Abstract: Sestrin-3, together with the other two members Sestrin-1 and Sestrin-2, belongs to the Sestrin family. The Sestrin protein family has been demonstrated to be involved in antioxidative, metabolic homeostasis, and even the development of nonalcoholic steatohepatitis (NASH). However, the adipogenic regulatory role of SESN3 in adipogenesis still needs to be further explored. In this study, we demonstrated SESN3 inhibited porcine pre-adipocyte proliferation, thus suppressing its adipogenesis. Meanwhile, SESN3 has b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…More importantly, our results revealed several potential ceRNA regulatory networks during bovine intramuscular preadipocyte differentiation. Among them, multiple studies have reported that SESN3, FOXO1, GPAM, and miR-27b regulate adipocyte differentiation and lipid metabolism [23][24][25][26]. Furthermore, the expression levels of SESN3, PELI2, GPAM and FOXO1 have been found to be regulated by the competitive binding of lncRNAs/ circRNAs and miRNAs in adipogenesis or other biological processes [23,[54][55][56][57][58].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…More importantly, our results revealed several potential ceRNA regulatory networks during bovine intramuscular preadipocyte differentiation. Among them, multiple studies have reported that SESN3, FOXO1, GPAM, and miR-27b regulate adipocyte differentiation and lipid metabolism [23][24][25][26]. Furthermore, the expression levels of SESN3, PELI2, GPAM and FOXO1 have been found to be regulated by the competitive binding of lncRNAs/ circRNAs and miRNAs in adipogenesis or other biological processes [23,[54][55][56][57][58].…”
Section: Discussionmentioning
confidence: 99%
“…Among them, multiple studies have reported that SESN3, FOXO1, GPAM, and miR-27b regulate adipocyte differentiation and lipid metabolism [23][24][25][26]. Furthermore, the expression levels of SESN3, PELI2, GPAM and FOXO1 have been found to be regulated by the competitive binding of lncRNAs/ circRNAs and miRNAs in adipogenesis or other biological processes [23,[54][55][56][57][58]. Finally, we further verified the expression of the genes in the ceRNA network by qRT-PCR, which demonstrated the reliability of the sequencing results in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation